Inter-phase charge and energy transfer in Ruddlesden–Popper 2D perovskites: critical role of the spacing cations. Issue 15 (29th March 2018) - Zheng, Kaibo; Chen, Yani; Sun, Yong; Chen, Junsheng; Chábera, Pavel; Schaller, Richard; Al-Marri, Mohammed J.; Canton, Sophie E.; Liang, Ziqi; Pullerits, Tõnu
Abstract : Photo-generated charge carrier dynamics in Ruddlesden–Popper 2D perovskites with linear ( n -BA) and branched (iso-BA) butylamine as spacing cations have been studied by using transient absorption and time-resolved photoluminescence spectroscopies. Abstract : Photo-generated charge carrier dynamics in Ruddlesden–Popper 2D perovskites with linear ( n -BA) and branched (iso-BA) butylamine as spacing cations have been studied by using transient absorption and time-resolved photoluminescence spectroscopies. Both n -BA and iso-BA perovskites consist of mixed-phase 2D quantum wells with various layer thicknesses, where the photo-generated charges undergo inter-phase charge transfer from thinner quantum wells to thicker ones. By shortening the spacer from n -BA to iso-BA, the transfer rates are significantly increased, which can also diminish the charge accumulation in thin quantum wells induced by the unbalanced electron and hole charge transfer rates. Under high excitation intensity, the shorter spacing cation is found to further facilitate the energy transfer, which can compete with fast high-order carrier recombination and consequently improve the charge transfer efficiency. Intriguingly, we observe the existence of extra bulk 3D phases embedded within iso-BA perovskites, which can efficiently collect the confined charges within 2D phases and then transport them with faster carrier mobility and slower recombination rates.